Regulating Water Transport Paths on Porous Transport Layer by Hydrophilic Patterning for Highly Efficient Unitized Regenerative Fuel Cells - Lee, Sung Min; Oh, Keun Hwan; Jeong, Hwan Yeop; Yu, Duk Man; Kim, Tae‑Ho (Nano-Micro Letters, 2025)
While unitized regenerative fuel cells (URFCs) are promising for renewable energy storage, their efficient operation requires simultaneous water management and gas transport, which is challenging from the standpoint of water management. Herein, a novel approach is introduced for examining the alignment hydrophilic pattern of a Ti porous transport layer (PTL) with the flow field of a bipolar plate (BP). UV/ozone patterning and is employed to impart amphiphilic characteristics to the hydrophobic silanized Ti PTL, enabling low-cost and scalable fabrication. The hydrophilic pattern and its alignment with the BP are comprehensively analyzed using electrochemical methods and computational simulations. Notably, the serpentine-patterned (SP) Ti PTL, wherein the hydrophilic channel is directly aligned with the serpentine flow field of the BP, effectively enhances oxygen removal in the water electrolyzer (WE) mode and mitigates water flooding in the fuel cell (FC) mode, ensuring uninterrupted water and gas flow. Further, URFCs with SP configuration exhibit remarkable performance in the WE and FC modes, achieving a significantly improved round-trip efficiency of 25.7% at 2 A cm−2. Highlights: 1 Novel amphiphilic patterned titanium porous transport layers (PTLs) significantly enhance the round-trip efficiency of unitized regenerative fuel cells (URFCs), achieving an impressive round-trip efficiency of 25.7% at a current density of 2 A cm-2. 2 The serpentine configuration of the patterned PTL excels in both fuel cell (FC) and water electrolyzer modes, resulting in a sevenfold increase in current density in FC mode compared to URFCs using hydrophilic pristine Ti PTLs.